2005
DOI: 10.4049/jimmunol.174.9.5537
|View full text |Cite
|
Sign up to set email alerts
|

BAFF Augments Certain Th1-Associated Inflammatory Responses

Abstract: B cell-activating factor belonging to the TNF family (BAFF; BLyS) is a critical regulator of B cell maturation and survival, and its overexpression in BAFF transgenic (Tg) mice results in the development of autoimmune disorders. BAFF also affects T cell function through binding to one of the BAFF receptors, BAFF-R. Using BAFF Tg mice, we examined a typical Th1-mediated response, the cutaneous delayed-type hypersensitivity reaction, and found a much greater degree of paw swelling and inflammation than in contro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
116
1
2

Year Published

2006
2006
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 129 publications
(123 citation statements)
references
References 56 publications
(60 reference statements)
4
116
1
2
Order By: Relevance
“…9,10 In addition, we also found rhBAFF could increase the production of IFN-␥ but had no obvious effect on the secretion of IL-4 in in vitro experiments, consistent with earlier studies showing typical Th1-mediated responses and reduced Th2-mediated responses in BAFF transgenic mice. 16 ITP is a heterogeneous disease; besides humoral immune abnormalities, several T-cell abnormalities have been demonstrated in patients with ITP, including Th1 bias, the inhibition of autologous megakaryocyte apoptosis by CD8 ϩ T cells, and cell-mediated cytotoxic lysis of platelets by CTLs. 3,4,[8][9][10]35 Our results indicated that elevated BAFF not only was involved in humoral immune abnormalities by promoting the survival of B cells, but also may be involved in the cellular immunity abnormalities by promoting the survival of T cells.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…9,10 In addition, we also found rhBAFF could increase the production of IFN-␥ but had no obvious effect on the secretion of IL-4 in in vitro experiments, consistent with earlier studies showing typical Th1-mediated responses and reduced Th2-mediated responses in BAFF transgenic mice. 16 ITP is a heterogeneous disease; besides humoral immune abnormalities, several T-cell abnormalities have been demonstrated in patients with ITP, including Th1 bias, the inhibition of autologous megakaryocyte apoptosis by CD8 ϩ T cells, and cell-mediated cytotoxic lysis of platelets by CTLs. 3,4,[8][9][10]35 Our results indicated that elevated BAFF not only was involved in humoral immune abnormalities by promoting the survival of B cells, but also may be involved in the cellular immunity abnormalities by promoting the survival of T cells.…”
Section: Discussionmentioning
confidence: 99%
“…[13][14][15] In addition, BAFF also augments certain Th1-associated inflammatory responses. 16 BAFF binds to 3 receptors: B-cell maturation antigen (tumor necrosis factor receptor superfamily, member 17 [TNFRSF17]), transmembrane activator and calcium-modulating cyclophilin ligand (CAML) interactor (TACI; TNFRSF13B), and BAFF receptor (BR3/BAFF-R; TNFRSF13C). 17,18 BR3, identified as the crucial receptor for B-cell survival, is expressed on a wide range of B-cell subsets, including immature, transitional, mature, memory, and germinal center B cells, as well as on plasma cells.…”
Section: Introductionmentioning
confidence: 99%
“…Over-expression of BAFF in mice and in humans is associated with autoimmune disorders such as Sjögren's syndrome (SS) and systemic lupus erythematosus (SLE) [4].…”
Section: Introductionmentioning
confidence: 99%
“…A potential role for BAFF in regulating T cell activation and function is also supported by in vivo studies. BAFF-transgenic (Tg) mice exhibit exaggerated T-dependent Ag responses, enhanced delayed-type hypersensitivity (DTH) responses, and have an expanded CD4 ϩ CD62L low , CD44 high memory population (9). Conversely, loss of BAFF signaling impairs the development of Ag-specific T cell responses (6).…”
mentioning
confidence: 99%